Sekolah Inklusif Berbasis Teknik Elektro: Desain Pendidikan Dreams Foundation untuk Pembangunan Berkelanjutan di Dompu - M. Ahleyani; Ranjiv A.A Sihombing; Shadeka Putratama Fidya; Andre Kurniawan Pratama; Aprilda Friana Pintu Batu (Yayasan Al-Afif, 2026)
This Study Aims To Examine The Design And Implementation Of Inclusive Electrical Engineering-Based Education Developed By The Dreams Foundation In Dompu Regency, West Nusa Tenggara, As Part Of A Sustainable Development Strategy. The Main Focus Of This Study Is How The Education Model Is Able To Provide Equal Access To Marginalized Community Groups Including Children From Underprivileged Families, Women, And Out-Of-School Youth To Acquire Vocational Skills In Electrical Engineering. A Qualitative Approach With A Case Study Method Is Used To Analyze The Curriculum Planning Process, Local Industry Involvement, And Its Impact On Reducing Social Inequality And Increasing Economic Mobility. The Results Show That The Inclusion-Based Approach Implemented By The Dreams Foundation Not Only Increases Access To Technical Education, But Also Strengthens The Social Networks And Economic Capacity Of The Target Community. These Findings Support The Achievement Of Sustainable Development Goals (Sdgs) Number 4 (Quality Education) And Number 10 (Reducing Inequality). This Study Recommends Replication Of This Model In Other Areas With Similar Challenges, Through Strategic Cross-Sector Partnerships